Efektifitas Model Pembelajaran Inkuiri untuk Mengukur Kemampuan Berpikir Logis Siswa Kelas IV pada Pembelajaran IPS di SD Negeri 08 Pedamaran - Nathasyah, Anisa; Idris, Muhamad; Suryani, Ida (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the effectiveness of the inquiry learning model to measure students' logical thinking skills in social studies class IV at SD Negeri 08 Pedamaran. This research is an experimental research form of pseudo experiment (Quasi Experiment), the research design used is a